2016
DOI: 10.4236/ce.2016.72035
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding Engagement in the Immersive t-MALL Classroom

Abstract: This paper focuses on engagement dynamics among foreign language students in coping within an immersive pedagogy in a tablet mobile assisted language learning (t-MALL) classroom ecology. This qualitative action research was implemented with 24 second-year undergraduates majoring in French as a foreign language in a Malaysian university. The pedagogical implementation included a task-based learning approach delivered according to personalized, meaningful and learner-controlled learning principles. In accordance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In recent years, mobile devices (e.g., smartphones, laptops, and pads) have been increasingly adopted by university language learners. Due to the portability and affordance of mobile devices, mobile-assisted language learning (MALL) has become ubiquitous among university students who engage in learning not only in formal contexts but also in informal learning contexts, such as self-directed language learning beyond the class ( Lai and Gu, 2011 ; Foomani and Hedayati, 2016 ; Gabarre et al, 2016 ; Taj et al, 2016 ). Research indicated that students are favorable to the use of mobile devices for language learning, and researchers have endeavored to study the effectiveness of mobile-assisted language learning (e.g., Lin and Lin, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, mobile devices (e.g., smartphones, laptops, and pads) have been increasingly adopted by university language learners. Due to the portability and affordance of mobile devices, mobile-assisted language learning (MALL) has become ubiquitous among university students who engage in learning not only in formal contexts but also in informal learning contexts, such as self-directed language learning beyond the class ( Lai and Gu, 2011 ; Foomani and Hedayati, 2016 ; Gabarre et al, 2016 ; Taj et al, 2016 ). Research indicated that students are favorable to the use of mobile devices for language learning, and researchers have endeavored to study the effectiveness of mobile-assisted language learning (e.g., Lin and Lin, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%